Direct maternal deaths attributable to HIV in the era of antiretroviral therapy: evidence from three population-based HIV cohorts with verbal autopsy. (15th July 2020) - Calvert, Clara; Marston, Milly; Slaymaker, Emma; Crampin, Amelia C.; Price, Alison J.; Klein, Nigel; Herbst, Kobus; Michael, Denna; Urassa, Mark; Clark, Samuel J.; Ronsmans, Carine; Reniers, Georges
Abstract : Objective: To assess whether HIV is associated with an increased risk of mortality from direct maternal complications. Design: Population-based cohort study using data from three demographic surveillance sites in Eastern and Southern Africa. Methods: We use verbal autopsy data, with cause of death assigned using the InSilicoVA algorithm, to describe the association between HIV and direct maternal deaths amongst women aged 20–49 years. We report direct maternal mortality rates by HIV status, and crude and adjusted rate ratios comparing HIV-infected and uninfected women, by study site and by ART availability. We pool the study-specific rate ratios using random-effects meta-analysis. Results: There was strong evidence that HIV increased the rate of direct maternal mortality across all the study sites in the period ART was widely available, with the rate ratios varying from 4.5 in Karonga, Malawi [95% confidence interval (CI) 1.6–12.6] to 5.2 in Kisesa, Tanzania (95% CI 1.7–16.1) and 5.9 in uMkhanyakude, South Africa (95% CI 2.3–15.2) after adjusting for sociodemographic confounders. Combining these adjusted results across the study sites, we estimated that HIV-infected women have 5.2 times the rate of direct maternal mortality compared with HIV-uninfected women (95% CI 2.9–9.5). Conclusion: HIV-infected women face higher rates of mortality from direct maternal causes, which suggests that we need to improve access to quality maternity care for these women. These findings also have implications for the surveillance of HIV/AIDS-related mortality, as not all excess mortality attributable to HIV will be explicitly attributed to HIV/AIDS on the basis of a verbal autopsy interview. Abstract : Supplemental Digital Content is available in the text